Regulation of cell therapy products in Korea. (April 2015) - Han, E.; Shin, W.
<x xml:space="preserve">Abstract</x> Cell therapy products are regulated by the Ministry of Food and Drug Safety under the Pharmaceutical Affairs Act in Korea. Sixteen cell therapy products including three stem cells were approved for marketing authorization, and 155 clinical protocols have been approved. Due to the lack of complete understanding of various cellular product characteristics and limited experience on these products, there are many regulatory challenges to the reliable evaluation of safety and efficacy of these products. These challenges include, not limited to, lack of appropriate animal model for preclinical studies, difficulty in translating preclinical results to clinical design, short half life and limited amount autologous cell samples for testing, difficulty in maintaining blindness of control group in clinical study especially when invasive operation is required, concern over tumor or ectopic tissue formation and so on. For various regulatory challenges, a regulatory approach is the risk‐based, case‐by‐case and science‐based review with flexibility, balancing risk and benefits. In addition to periodic safety update reporting after marketing authorization, re‐examination of a drug and re‐evaluation of a drug exist to monitor the safety of an approved drug. There is a system for cell therapy product only, which requires mandatory safety reporting for every use of the approved cellular product for specific time period.